2006
DOI: 10.1111/j.1468-1331.2006.01187.x
|View full text |Cite
|
Sign up to set email alerts
|

Early admission to stroke unit influences clinical outcome

Abstract: An improvement in patient arrival time to stroke unit (SU) is recommended, since earlier stroke management seems to improve 'per se' functional outcome. The objective of this study was to determine if early admission influences the outcome, reduces disability and mortality at discharge and three months later independent of tlirombolytic treatment. Consecutive acute stroke patients admitted to SU between January 1st 2000 and December 31st 2003 were studied in order to analyze the actual role of acute management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
44
2
3

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 34 publications
4
44
2
3
Order By: Relevance
“…Ischemic stroke patients with severer initial disability have a tendency to visit hospitals earlier [5,6,7,8,9,10,11,12], and severe initial disability is a known predictor of a poor chronic outcome [17,18,19,20,21]. Thus, patients with earlier hospital arrival were reported to have a poorer outcome [5, 6], as was shown in the present unadjusted results.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Ischemic stroke patients with severer initial disability have a tendency to visit hospitals earlier [5,6,7,8,9,10,11,12], and severe initial disability is a known predictor of a poor chronic outcome [17,18,19,20,21]. Thus, patients with earlier hospital arrival were reported to have a poorer outcome [5, 6], as was shown in the present unadjusted results.…”
Section: Discussionsupporting
confidence: 65%
“…However, previous studies have generally shown that patients who arrived at a hospital early after ischemic stroke onset had a worse functional outcome and higher mortality than those who arrived later [5, 6]. Major causes of this discouraging result might be that stroke patients with severer initial disability have a tendency to visit a hospital earlier [5,6,7,8,9,10,11,12], as well as the fact that previous studies did not adjust patient outcome for initial neurological severity. Although intracerebral hemorrhage (ICH) is associated with a poorer outcome than ischemic stroke, the positive relationship between early hospital visit and initial severity was reported only in studies based on relatively small numbers of patients [13, 14].…”
Section: Introductionmentioning
confidence: 87%
“…In Western European countries about 30–40% of patients arrived at hospital within 3 h of stroke onset [20, 21]. Considering groups I and II, our results suggest a similar percentage of patients hospitalized within the 3-hour time frame.…”
Section: Discussionsupporting
confidence: 64%
“…Acute ischemic stroke should be considered to be an emergency condition, and the outcome and prognosis is influenced by an early hospital arrival [1,2]. Early stroke treatment has become an important issue after the study finding that an intravenous injection of tissue-type plasminogen activator (t-PA) is effective in patients with all types of acute ischemic stroke when administered within 3 h after the onset of symptoms [3].…”
Section: Introductionmentioning
confidence: 99%